APLIKASI PENJUALAN SPAREPART MOTOR BERBASIS WEB PADA PT BINTAN SENTOSA INDAH - Hendi Setiawan; Heti Mulyani; Ahmad Afandi (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2018)
Entering this increasingly modern world, information technology is advancing rapidly. With the existence of computers that were created to facilitate human work to achieve good results in making hardware and software. PT. Bintan Sentosa Indah requires an information system that supports and provides satisfying services to consumers. For this reason the author makes a final project regarding the motorcycle spare parts sales system at PT. Bintan Sentosa Indah. PT. Bintan Sentosa Indah is a business entity engaged in the service and sale of motorcycle spare parts. At PT. Bintan Sentosa Indah, the process of selling spare parts is still done manually. This of course requires a fairly long process. Sales records that are still manually input by the cashier are ineffective, because data retrieval takes time and can result in human errors. This information system design can solve problems that have been in PT. Bintan Sentosa Indah. So that this system can facilitate the process of selling spare parts more effectively and efficiently, not limited by time and geographic reach. The software used as a tool in this research is to use PHP and the methodology used for the development of this application is to use the Waterfall paradigm.